Criminal Christianities - Creech, David A. (Word & world, 2018)
Early Christian sources often comment on the need to visit and care for those who are imprisoned, as it is very likely that this was an all-too-frequent experience for the followers of Christ in the early church. Christians saw the very real need of providing for those of their community who were imprisoned for their Christian faith.